Calcium hydroxide as intracanal dressing for teeth with apical periodontitis - Sari Dewiyani (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: Root canal infection and periapical diseases are caused by bacteria and their products. Long term infection may spread bacteria throughout the root canal system. Apical periodontitis caused by infectious microbe that persistent in root canals can cause radiographic and histopathology periapical changes. Chemomechanical preparation and intracanal dressing then are recommended to be conducted and used in between visits to eliminate microbes in root canals. Calcium hydroxide (Ca(OH)2) can be used as intracanal dressing since it can be used as musical physical defense barrier to eliminate re-infection in root canal and to disturb nutrition supply for bacterial development. Purpose: The aim of this study is observe the effectiveness of Ca(OH)2 in treating endodontic teeth with apical periodontitis. Cases: Case 1 and 3 are about patients whose left posterior mandibular teeth had spontaneous intermittent pain. Case 2 is about a patient whose left posterior maxillary teeth had gingival abscess and fracture history. Based on the radiographic examination, it was known that the filling of root canal was incomplete and there was radiolucency in the apical area. Case management: The cases were treated with triad endodontics, which involves preparation, disinfection by using 2.5% NaOCl as irrigation substance and calcium hydroxide as intracanal dressing, and then the filling of root canal with gutta percha and endomethasone root canal cement. Evaluations were conducted one month, 12 months, and 24 months after the treatment. Conclusion: Calcium hydroxide is effective to be used as intracanal dressing in apical periodontitis cases.Latar belakang: Infeksi saluran akar dan penyakit periapeks disebabkan oleh mikroba dan produknya. Infeksi yang berlangsung lama memungkinkan bakteri masuk ke dalam seluruh sistem saluran akar. Periodontitis apikal disebabkan oleh infeksi persisten mikroba di dalam sistem saluran akar disertai perubahan radiografik dan histopatologik periapeks. Preparasi kemomekanis dan penggunaan obat saluran akar antar kunjungan sangat dianjurkan untuk mengeleminasi mikroba dalam saluran akar. Kalsium hidroksida merupakan obat saluran akar karena dapat berperan sebagai barrier pertahanan fisik, mencegah infeksi ulang dan mengganggu suplai nutrisi untuk perkembangan bakteri. Tujuan: Untuk membuktikan efektifitas kalsium hidroksida pada perawatan gigi dengan periodontitis apical yang disertai dengan keluhan sakit dan adanya gambaran radiolusensi di periapikal. Kasus: Kasus 1 dan 3 adalah penderita dengan keluhan gigi belakang bawah kiri sakit dengan nyeri spontan hilang timbul, kasus 2 adalah penderita yang gigi depan atas terdapat benjolan di gusi dan riwayat fraktur. Pada pemeriksaan radiografis terlihat pengisian saluran akar yang tidak sempurna dan gambaran radiolusensi di apikal. Tatalaksana kasus: Pada kasus ini dilakukan tindakan triad endodontik, yaitu preparasi saluran akar, desinfeksi dengan larutan irigasi NaOCl 2,5% dan obat intrakanal kalsium hidroksida disertai dengan pengisian saluran akar dengan gutta percha dan semen saluran akar endomethason. Evaluasi dilakukan 1 bulan, 12 bulan, dan 24 bulan. Kesimpulan: Kalsium hidroksida efektif sebagai obat intrakanal pada kasus periodontitis apikal.